Dampak Label Halal Palsu Terhadap Kepercayaan Konsumen dan Reputasi Bisnis Lokal - Syahira Rachmadina; Halimah Zahrah; Fidelairna Daniswara; Umu Mahmudah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Consumer trust is a crucial element in the sustainability of culinary businesses, especially in Indonesia, where the majority of the population is Muslim. The case of Ayam Goreng Widuran Solo, a long-established traditional restaurant, gained public attention after it was revealed that one of its menu items contained pork, without clear labeling or information provided to consumers. This study aims to analyze the impact of a lack of transparency in food content information on consumer trust, business, and compliance with halal product regulations. This research employs a qualitative descriptive approach, using semi-structured interviews and documentation studies from social media and online news sources. Data were analyzed thematically by identifying patterns in consumer perceptions and responses. The findings indicate that the absence of transparent product information significantly undermines consumer trust, triggers reputational crises on social media, and suggests potential violations of Law No. 33 of 2014 concerning Halal Product Assurance. Moreover, the study reveals that many small business operators still lack understanding of regulatory obligations regarding halal and non-halal labeling. This research highlights the importance of business ethics and information transparency in maintaining consumer trust, particularly in a religiously sensitive society. Greater education and regulatory oversight are needed to ensure comprehensive implementation of halal standards, not only in large industries but also within traditional food enterprises.